Development of Secure Communication Protocol for IOT Device - Kokate Ankita; Labade Prerana; Khedkar Vaishnavi; Dr. Date A.R; Dr. Divekar S.N (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research paper presents a novel approach to Bluetooth connectivity focused on enhancing security and user control through a single-connection enforcement mechanism. The system prevents multiple simultaneous connections, thereby mitigating risks associated with unauthorized device access and data breaches. It employs AES encryption for secure data transmission and UUID-based authentication to ensure that only trusted devices can establish a connection. Through a combination of rigorous technical design and user-centric principles, our approach addresses inherent vulnerabilities in conventional Bluetooth networks, aiming to deliver a robust and reliable connectivity solution in environments ranging from smart homes to healthcare applications. The paper discusses the comprehensive architecture and methodology behind the secure Bluetooth connectivity system, integrating both hardware and software perspectives. A detailed review of existing literature in the domain underpins our research, providing context and justification for the proposed system. The study not only highlights the technical efficacy of the solution but also underscores the importance of human-centric design in achieving a seamless and secure user experience. The results demonstrate significant improvements in connection reliability and security, paving the way for further advancements in Bluetooth-enabled technologies.
Keywords: Bluetooth Connectivity; Secure Bluetooth; AES Encryption; Single Connection Enforcement; UUID Authentication; Device Discovery; Secure Disconnection; IoT Security; Smart Device Security; Human-Centric Design